Improving Inpatient Medication Adherence Using Attendant Education In A Tertiary Care Hospital In Uganda - Alupo, Patricia; Ssekitoleko, Richard; Rabin, Tracy; Kalyesubula, Robert; Kimuli, Ivan; Bodnar, Benjamin E. (International Journal for Quality in Health Care, 2017)
Although widely utilized in resource-rich health care systems, the use of quality improvement (QI) techniques is less common in resource-limited environments. Uganda is a resource-limited country in Sub-Saharan Africa that faces many challenges with health care delivery. These challenges include understaffing, inconsistent drug availability and inefficient systems that limit the provision of clinical care.Poor adherence to prescribed inpatient medications was identified as a key shortcoming of clinical care on the internal medicine wards of Mulago National Referral Hospital, Kampala, Uganda. Baseline data collection revealed a pre-intervention median inpatient medication adherence rate of 46.5% on the study ward. Deficiencies were also identified in attendant (lay caretaker) education, and prescriber and pharmacy metrics.A QI team led by a resident doctor and consisting of a QI nurse, a pharmacist and a ward nurse supervisor used standard QI techniques to address this issue.Plan-Do-Study-Act cycle interventions focused on attendant involvement education, physician prescription practices and improving pharmacy communication with clinicians and attendants.Significant improvements were seen with an increase in overall medication adherence from a pre-intervention baseline median of 46.5% to a post-intervention median of 92%. Attendant education proved to be the most effective intervention, though resource and staffing limitations made institutionalization of these changes difficult.QI methods may be the way forward for optimizing health care delivery in resource-limited settings like Uganda. Institutionalization of these methods remains a challenge due to shortage of staff and other resource limitations.